Ecopathogenic complexes of American trypanosomiasis in endemic areas of Venezuela: Diagnosis and variability of Trypanosoma cruzi (2019)
Background & objectives: Trypanosoma cruzi, the causative agent of American trypanosomiasis, has been reported in 180 mammalian species and 154 triatomines species of Neotropic. This is a clonal parasite with variable biological behaviour, associated with the genetics of the parasite and its hosts. To know the eco-pathogenic complex of this zoonosis, it was proposed to characterize T. cruzi isolates obtained from triatomines and domestic, peridomestic and wild mammals of the eastern and central-western regions of Venezuela. Methods: The positivity to T. cruzi was established and the isolates were genetically characterized by PCR amplification of the mini-exon gene, the DNA coding for 24Sα and 18S rRNA, and polymorphic sequences-RFLPs. The sampling sites were georeferenced using the MapSource Software and ArcGis 9.3 programs to generate distribution maps of the isolates. Results: Of the 460 hosts (205 triatomines and 255 mammals), 49% were positive for the parasite. On the other hand, 38 isolates obtained from the triatomines and 23 isolates obtained from mammals were evaluated. The TcI genotype predominated in most of the isolates; however, in those obtained from triatomines the presence of the TcIII genotype in single infections and TcI + TcIII or TcI + TcIV in mixed infections was also evidenced. Interpretation & conclusion: There is a possibility that the triatomines act as biological syringes for these genotypes associated exclusively to them. The heterogeneity in T. cruzi isolates demonstrated the complexity of parasitosis in these regions, presenting its control and prevention as a challenge.